In situ, real-time measurements of contact pressure internal to jointed interfaces during dynamic excitation of an assembled structure. (November 2021) - Dreher, T.; Brake, M.R.W.; Seeger, B.; Krack, M.
Highlights: An electronic pressure film is used to measure normal contact pressures within a jointed interface. Measurements show that the interfacial contact area decreases as bolt torques increase. The contact pressures are found to vary significantly for all parts of the interface. The contact pressure changes in the interface are significantly different for transient and steady-state excitations. Evidence of non-stationary waves is also found. Previously reported experimental and numerical studies strongly support the new measurements. Abstract: Despite the ubiquitousness of jointed structures, the nonlinear interfacial behavior within bolted joints is still an insufficiently studied and poorly understood environment. For the development of effective simulation approaches, a deeper understanding of the salient physical effects within the contact surface is needed. This work studies the interfacial pressure distribution and pressure changes during static and dynamic loading within the contact interface of a bolted structure. An electronic pressure sensor is placed in the interface plane. After analyzing to what extent the system's nonlinear stiffness and normal kinematics are changed by the measurement equipment, real-time measurements of the contact pressure are made for both impact hammer and sinusoidal shaker testing (both swept sine and steady-state excitations). The measurements invalidate many commonly held assumptions for contact models that were based on observations from static pressure films.